Building Partnership to Improve Migrants’ Access to Healthcare in Mumbai - Gawde, Nilesh Chandrakant; Sivakami, Muthusamy; Babu, Bontha V. (Frontiers in Public Health, 2015)
Objectives: An intervention to improve migrants’ access to healthcare was piloted in Mumbai with purpose of informing health policy and planning. This paper aims to describe the process of building partnership for improving migrants’ access to healthcare of the pilot intervention including the role played by different stakeholders and the contextual factors affecting the intervention. Methods: The process evaluation was based upon Baranowski and Stables’ framework. their Observations in community and conversations with stakeholders as recorded in daily diaries, minutes of pre-intervention workshops and stakeholder meetings served as data sources. Data were coded using the framework and descriptive summaries of evaluation components were prepared. Results: Recruitment of stakeholders was easier than sustaining their interest. Community representatives led the intervention assisted by government officials. They planned community level interventions to improve access to healthcare which involved predominantly information, education and communication activities for which pre-existing formal and informal social networks and community events were used. Although the intervention reached migrants living with families, single male migrants neither participated nor did the intervention reach them consistently. Contextual factors such as culture differences between migrants and native population and illegality in the nature of the settlement resulting in the exclusion from services were the barriers. Conclusion: Inclusive multi-stakeholder partnership including migrants themselves and using both formal and informal networks in community is a feasible strategy for health education and has potential to improve the migrants’ access to healthcare. However, there are challenges to the partnership process and new strategies to overcome these challenges need to be tested such as peer-led models for involvement of single male migrants. For sustaining such efforts and mainstreaming migrants, addressing contextual factors and having formal mechanisms for their inclusion are equally important.